Knot again - Jackson, K. M. (Jove, 2022)
"Each day is rinse and repeat for fireman Lucas Strong until a fateful run-in at his local laundromat. Hoping to attract more customers to his family's knitting shop, Lucas Strong participated in an FDNY charity calendar and accidentally became a local celebrity. The only place he can find solace is Scrubs-a 24/7 laundromat where he can disappear for a couple of hours. But Lucas's soapy sanctuary is shaken by an inquisitive little girl with a late-night interest in knitting whose mother is his old school crush. Sidney Harris-Hughes knows that Harlem is like any other small town, and everyone is probably whispering about how she left such a good man-and a good life-behind to wash and fold laundry by the pound. If only they knew the truth. But Sidney will always put her daughter's happiness first, even if that means moving back to Harlem and facing her past. What Sidney never expected was to see Lucas Strong again. A long-forgotten attraction kicks into high gear as Lucas and Sidney start to spend time together at the laundromat, and they must decide if this is true love or just an infatuation, thin and as fragile as a soap bubble"--